Presence of high-risk nano particulate matters in powder injection: microscopic evaluation and investigation of particles contamination - Yasir Mehmood; Jacky Ho; Hira Shahid; Mohammed H. AL Mughram; Musaab Dauelbait; Mohammed Bourhia (Scientific Reports)
Abstract To analyse the health hazard particles in injection. By using different analytical techniques, we have found nanoparticles within injections. Complex parenteral products are prone to particulate issues that may pose safety and quality risks. The pharmaceutical quality of powder injections (ceftriaxone sodium) regarding particle contamination was assessed. We have selected ceftriaxone sodium because it is widely used all over the world. The powder is contained within a vial made of colourless Type II glass, which is sealed with a grey bromobutyl rubber stopper and further secured with an aluminium pilfer-proof cover. Our study primarily concentrated on particulate matter in powder injectable products. Particulate contaminants include fibres, dust, glass, and silicone. The incorporation of these components into drug products primarily occurs during the manufacturing process. The findings of our analysis indicate that the majority of the injection parameters were in accordance with the specified requirements. In some brands, we found visible particles that we further evaluated by microscopy, liquid particle counters, and FTIR, and the results showed that some kinds of fibres, glass, and silica were found (60%). Invisible 10 μm particles (limit < 6000) were also observed and determined to be of specifications in some brands (14%).